2022
DOI: 10.1002/ldr.4149
|View full text |Cite
|
Sign up to set email alerts
|

Excessive livestock grazing overrides the positive effects of trees on infiltration capacity and modifies preferential flow in dry miombo woodlands

Abstract: The increase in livestock grazing in African drylands such as miombo woodlands threatens land productivity and ecosystem functioning. Trees have positive effects on soil hydraulic properties, but few studies have looked at grazing intensity and hydrological functioning in different land uses. Therefore, we conducted a biophysical survey in Morogoro Rural District, Tanzania, where we identified four main land uses and land cover types, that is, Forest reserve, open-access forest, cropland under fallow, and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 71 publications
(95 reference statements)
6
12
0
Order By: Relevance
“…Furthermore, the activity of soil fauna and roots enhances soil aggregation and macroporosity, leading to improved soil water conductivity and drainage (Belsky et al, 1993;Benegas, 2013). Our findings support previous studies which have shown increased soil infiltration capacity with tree cover in various tropical ecosystems (Bargués-Tobella et al, 2014;Benegas, 2013Benegas, & 2018Ilstedt et al, 2016;Lulandala et al, 2021). Tree removal typically reduces the quantity and quality of organic matter input and increases soil surface exposure to rainfall and sunlight (Bhuyan & Laskar, 2020), which can result in higher impact from raindrops and crust formation at the soil surface, leading to lower infiltration and increased surface runoff and erosion (Aber et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the activity of soil fauna and roots enhances soil aggregation and macroporosity, leading to improved soil water conductivity and drainage (Belsky et al, 1993;Benegas, 2013). Our findings support previous studies which have shown increased soil infiltration capacity with tree cover in various tropical ecosystems (Bargués-Tobella et al, 2014;Benegas, 2013Benegas, & 2018Ilstedt et al, 2016;Lulandala et al, 2021). Tree removal typically reduces the quantity and quality of organic matter input and increases soil surface exposure to rainfall and sunlight (Bhuyan & Laskar, 2020), which can result in higher impact from raindrops and crust formation at the soil surface, leading to lower infiltration and increased surface runoff and erosion (Aber et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…In our study area, forest roads are mainly used by people, motorcycles, livestock, and sometimes tractors coming and going from the forest to transport charcoal and timber. The decrease in infiltration capacity near the road could be explained by loss of tree cover, which may be due to illegal tree cutting for building material (poles) or firewood collection (Manyanda et al, 2021), frequent movement of livestock, and grazing (Lulandala et al, 2021). Both illegal cutting and livestock grazing lead to biomass removal, which may, in turn, decrease soil organic matter and SOC stock (Devi, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in river discharge may be the effect of replacing the Amazon forest and cerrado for pasture expansion, with possible longterm consequences for the regional hydrological cycle. Such hydro-environmental relationships are due to the fact that the soil of the areas destined for the activities usually becomes more compact, hindering the process of water infiltration and, consequently, increasing the surface runoff (Lulandala et al, 2021). The urban area × flow (r = 0.46) has a low direct and positive correlation, in which the increase in flow consists of a decrease in soil infiltration conditions.…”
Section: La Niñamentioning
confidence: 99%
“…According to the theoretical framework of sustainable livelihood and sustainable development, humans' livelihood assets are the natural ecology within the scope of human activities (Huq et al, 2020; Lusseau & Mancini, 2019), and their livelihood strategy is to highly develop and utilize natural assets. Due to its low economic benefits, this approach can only meet the livelihood needs and cannot restore and build natural ecology, leading to the reduction of ecological assets (Barbier & Hochard, 2018; Lulandala et al, 2022). If there is no other livelihood strategy and livelihood needs continue to increase, utilizing more natural assets becomes the only means of survival.…”
Section: Introductionmentioning
confidence: 99%